Quality of Life among type 2 Diabetes Mellitus Patients in Song Phi Nong District, Suphan Buri Province - On-onpapakul, Phudit; Kahanak, Sridharan (Journal of Public Health and Innovation, 2026)
The research study on the quality of life of diabetic patients with uncontrolled blood glucose levels in Song Phi Nong District, Suphan Buri Province aimed to examine the level of quality of life among diabetic patients whose blood glucose levels could not be controlled in Song Phi Nong District, Suphan Buri Province. It also aimed to investigate the relationships between personal factors, knowledge about diabetes, and self-care practices and the quality of life of diabetic patients with uncontrolled blood glucose levels in the area. The sample consisted of 368 diabetic patients with uncontrolled blood glucose levels in Song Phi Nong District, Suphan Buri Province. Data were collected using a questionnaire. The data were analyzed using descriptive statistics, including frequency distribution and percentage. The study hypotheses were tested using the Spearman’s Rank Correlation test. The research findings revealed that the overall quality of life of the sample group was at a high level (Mean = 104.09, S.D. = 13.391). When considered by dimension, the aspects with high levels of quality of life were vitality and energy (Mean = 30.48, S.D. = 0.396), diabetes control (Mean = 28.56, S.D. = 14.060), anxiety (Mean = 10.26, S.D. = 5.239), and sexual functioning (Mean = 5.81, S.D. = 3.538), respectively. The aspect with a low level of quality of life was social burden (Mean = 29.01, S.D. = 4.355). The sample group’s knowledge about diabetes was significantly associated with the social burden dimension of quality of life at the 0.05 level (p-value = 0.029). In addition, the self-care practices of the sample group were significantly associated with overall quality of life at the 0.05 level (p-value = 0.008). Recommendations: The findings of this study can be used to guide the planning and development of educational service models for patients, as well as to enhance diabetes health literacy. Improving patients’ knowledge and understanding of diabetes will enable them to apply this information effectively in managing their condition.